The role of breastfeeding practices as part of reproductive health in preventing stunting in toddlers aged >24 months - Nelly Indrasari; Eva Berliana; Amrina Octaviana; Indah Trianingsih; Risneni Risneni (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Stunting is a chronic nutritional problem that impacts child growth and development and is an important indicator of reproductive health. Optimal breastfeeding practices, such as Early Initiation of Breastfeeding (IMD), exclusive breastfeeding, and breastfeeding until two years of age, are part of reproductive health interventions that play a role in preventing stunting. Purpose: To analyze the role of breastfeeding practices as part of reproductive health in preventing stunting in toddlers aged 24-59 months. Method: This study used a correlational analytical design with a cross-sectional approach. The study population was 1,497 toddlers, with a sample of 94 respondents selected using a purposive sampling technique. Data were collected through questionnaires and anthropometric measurements, then analyzed using the chi-square test with a significance level of 0.05. Results: The study showed a significant association between breastfeeding practices and stunting, including early initiation of breastfeeding (IMD) (p=0.001; OR=0.175), exclusive breastfeeding (p=0.001; OR=0.023), and breastfeeding until 24 months of age (p=0.001; OR=0.089). Overall, successful breastfeeding practices as part of reproductive health were significantly associated with stunting (p=0.001; OR=0.019), with toddlers who received optimal breastfeeding practices having a 98.1% lower risk of stunting. Conclusion: Thus, breastfeeding practices are a crucial component in efforts to prevent stunting in toddlers, particularly within the framework of reproductive health interventions